Slow Learner Student Profile (Case Study at MAN 1 Padang Lawas) - Anna Mupida; Asmidir Ilyas (Current Issues in Counseling, 2021)
This research is motivated by the phenomenon of students who are slow in learning, for example: slow in accepting or capturing learning, slow in managing lessons, slow reading, slow reading comprehension, slow working, slow doing assignments, slow in solving problems and so on. Children who are slow to learn are called slow learners. The inability of these students will affect themselves and affect others. The purpose of this study were (1) To describe the case of slow learner students, (2) to determine the form of slow learner student delay, (3) to determine the case study of slow learner students. This type of research is a qualitative descriptive study in the form of a case study. The subjects in this study were five students at MAN 1 Padang Lawas North Sumatra. The data collection instruments used in this study were interview, observation, and documentation guidelines. The data analysis technique used in this research is thematic analysis by conducting transcripts of interviews that have been verbatim. The results of this study reveal the profile of the slow learner students carried out, the five subjects were unable to achieve their learning objectives in the process or their learning activities, the five subjects had difficulty memorizing, counting, and several other obstacles. Unlike other students in their socialization, the five subjects preferred to be silent and did not play an active role in the class. Meanwhile, their emotional uncontrollable causes they cannot achieve their goals in learning well. Based on the research results, it is suggested that guidance and counseling teachers can be used as a guideline in determining the delivery of BK services, especially those related to slow learner students through information services, content mastery services and individual counseling services.